Determining TQM practices in university R&D activities using factor analysis: Research experience of Malaysian universities - Jusoh, Ahamad; Yusoff, Rushami Zien; Mohtar, Shahimi (Universiti Teknologi Malaysia, 2008)
Overall, this paper discusses the applicability of TQM and proposes a theoretical framework of TQM to suit the need of the Research and Development (R&D) context. The dimensions for the framework were based on the previous empirical studies, the evaluation criteria of world standard criteria such as MBNQA, EFQM, and QMS ISO 9000, and quality concept from the experts. In order to understand the TQM practices in R&D environment, this paper addresses the need for the study from the university researchers’ perspective. Data were collected through a large-scale mail survey from academic researchers of four Malaysian Research Universities. The constructs of TQM practices were validated and determined using factor analysis. The findings from this study suggest that the seven dimensions i.e. top management leadership, data and information management, performance management, process management, partnership, customer focus and resource management are sufficient to explain the TQM practices in R&D context.